Pembentukan Hukum dan Perlakuan Khusus Wilayah Provinsi Kepulauan dalam Sistem Pemerintahan Daerah di Indonesia - Zainuri (Faculty of Law Hang Tuah University, 2018)
In the era of regional autonomy for regional governments to build the island province region based on: (a) There are as many as 60% of the population or as many as 140 million Indonesians live in coastal areas. Where 22% of them live in coastal and remote islands that have been less touched by development, (b), the development policy approach in Indonesia has been carried out with a land-oriented regional development approach whereas Indonesia is an archipelago therefore a different approach is needed for development in the island province, (c), Difficulties in Regional Control Patterns. In the Province, land-based communication is much easier to do, while communication is far more difficult to do in the island province, (d), the difficulty of the local government in empowering small islands in the island province especially those in the border region, (e), still Isolation of the archipelago community that has not been touched by development. In this paper the author uses a normative juridical approach with legal issues in this paper is the formation of law and special treatment of the island province in the system of regional government. Special arrangements and treatment of the Islands Province, because in Law No. 23 of 2014 concerning Regional Governments has not specifically regulated the island Province.